The Palliative Management of Refractory Cirrhotic Ascites Using the PleurX© Catheter - Jason Reinglas; Kayvan Amjadi; Bill Petrcich; Franco Momoli; Thomas Shaw-Stiffel (Canadian Journal of Gastroenterology and Hepatology)
Background. Treatment options are limited for patients with refractory cirrhotic ascites (RCA). As such, we assessed the safety and effectiveness of the PleurX catheter for RCA. Methods. A retrospective analysis was performed on all patients with RCA who have undergone insertion of the PleurX catheter between 2007 and 2014 at our clinic. Results. Thirty-three patients with RCA were included in the study; 4 patients were lost to follow-up. All patients were still symptomatic despite bimonthly large volume paracentesis and were not candidates for TIPS or PV shunt. Technical success was achieved in 100% of patients. The median duration the catheter remained in situ was 117.5 days, with 95% CI of 48–182 days. Drain patency was maintained in 90% of patients. Microorganisms consistent with spontaneous bacterial peritonitis (SBP) from a catheter source were isolated in 38% of patients. The median time to infection was 105 days, with 95% CI of 34–233 days. All patients were treated for SBP successfully with antibiotics. Conclusion. Use of the PleurX catheter for the management of RCA carries a high risk for infection when the catheter remains in situ for more than 3 months but has an excellent patency rate and did not result in significant renal injury.